2020
DOI: 10.1097/brs.0000000000003511
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prolonged Opioid Use and Effects of Opioid Tolerance on Clinical Outcomes After Anterior Cervical Discectomy and Fusion Surgery

Abstract: Study Design. Retrospective study. Objective. The aim of this study was to determine risk factors for prolonged opioid use and to investigate whether opioid-tolerance affects patient-reported outcomes following anterior cervical discectomy and fusion (ACDF) surgery. Summary of Background Data. There is a lack of consensus on risk factors that can affect continued opioid use after cervical spine surgery and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…9 Among surgical specialties, orthopedic and neurosurgery procedures tend to have the highest rates of opioid use, and interventional spinal procedures fall at the intersection of these specialties. 10 Over the past three decades, the diagnoses and treatment of spinal pathologies, such as lumbar stenosis and spondylolisthesis, have increased as the United States experiences an aging population. 11 Meanwhile, opioid use following common procedures such as spinal and/or lumbar fusion operations is strikingly high.…”
Section: Introduction Opioid Epidemic and Sequelaementioning
confidence: 99%
“…9 Among surgical specialties, orthopedic and neurosurgery procedures tend to have the highest rates of opioid use, and interventional spinal procedures fall at the intersection of these specialties. 10 Over the past three decades, the diagnoses and treatment of spinal pathologies, such as lumbar stenosis and spondylolisthesis, have increased as the United States experiences an aging population. 11 Meanwhile, opioid use following common procedures such as spinal and/or lumbar fusion operations is strikingly high.…”
Section: Introduction Opioid Epidemic and Sequelaementioning
confidence: 99%
“…These findings could represent potentially modifiable risk factors for orthopaedic surgeons to help prevent the Numerous previous studies have evaluated risk factors for prolonged opioid use after orthopaedic surgery; however, most of these studies focus on patient-specific risk factors, such as medical comorbidities and prior opioid use. [17][18][19][20] In hand surgery specifically, studies have identified preoperative opioid use, alcohol use, smoking history, younger age, lower income, psychiatric disorders, benzodiazepine use, and higher comorbidity scores as risk factors for prolonged postoperative opioid use. 17,18,28 However, very few studies could be identified that investigate how opioid-prescribing patterns of the operating surgeon may contribute to prolonged opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have evaluated risk factors for prolonged opioid use after orthopaedic surgery; however, most of these studies focus on patient-specific risk factors, such as medical comorbidities and prior opioid use. 17 18 19 20 In hand surgery specifically, studies have identified preoperative opioid use, alcohol use, smoking history, younger age, lower income, psychiatric disorders, benzodiazepine use, and higher comorbidity scores as risk factors for prolonged postoperative opioid use. 17 , 18 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to studies published by Adogwa et al and Massie et al, Harris et al found that the rates and duration of chronic opioid use were highest in the Western US ( p -value < 0.001). Additionally, pre-operative opioid, drug abuse, depression, and anxiety were all risks factors of chronic opioid use [ 53 , 59 , 60 ].…”
Section: Geographymentioning
confidence: 99%